History, gender and ‘new practices of self’: re-interpreting Namibia’s Independence war through the work of Tuli Mekondjo and Helena Uambembe - Taylor, Julie J (My University, 2021)
The biographies of artists Tuli Mekondjo and Helena Uambembe have been fundamentally shaped by Namibia’s War of Independence (1966 - 1990), during which their respective families were ‘on opposite sides’. The history of this transnational war has been primarily told by political parties, historians and white male military autobiographers. Far less so has it been told by photographers and visual artists, but again this has mostly been by white men. Mekondjo and Uambembe stand out in this context as pioneers. Both artists draw on the photographic archive to create mixed media work, employ gendered modalities such as embroidery and sewing, and have a performance practice. As such, they appear to form part of a growing group of avant garde artists across southern African whose practices have been posited by Brandt (2020) as “new practices of self”, creating new historical, feminist, decolonial and spiritual vantage points on the War whilst resisting state-driven “patriotic histories”. The artists’ work goes beyond a simple insertion of black women’s voices into dominant or contested narratives about the past: they operate as parallel revisionists themselves, shaping new types of history-telling in dialectic relationships with historical scholarship and, in the case of Mekondjo, through spiritual practices. Drawing on recent revisionist socio-military histories, this research interrogates layers of absence in artistic, gendered and transnational perspectives on Namibia's Independence War. It also asks how engaging with the work of Mekondjo and Uambembe might help us address historiographic and theoretical absences about Namibia’s marginalised place in the South African imagination, and in art history in particular.
This research report is submitted in partial fulfilment of the requirements for the degree of Master of Arts in History of Art by Coursework and Research Report to the Faculty of Humanities, School of Arts, University of Witwatersrand, Johannesburg, 2021